Uniformed Services University Medical Student Mentorship Experiences and Gender From 2010 to 2017. Issue 7 (6th May 2020) - Latham, Kerry; Dong, Ting; Schreiber, Deanna; Torre, Dario; Durning, Steve; Battista, Alexis
Abstract: Introduction: Gender disparity in medicine has drawn increased attention in the form of root cause analysis and programmatic solutions with the goal of equity. Research indicates that mentoring, guidance, and support, which include the provision of social and academic guidance and support from more experienced practitioners, can mitigate challenges associated with gender disparity. The purpose of this study was to explore women medical students' self-reports of mentorship during their time at Uniformed Services University (USU), if women report similar levels of mentorship as compared to men, and if levels of characteristics associated with mentoring (eg, social support, academic guidance) changed over time. Materials and Method: Using data from the American Association of Medical College's Graduate Questionnaire, a survey sent to all medical students prior to graduation, items were coded as related to mentorship, guidance, and support and analyzed to compare responses of female and male students from graduating USU classes of 2010–2017. Results: No significant difference was found between experiences of female and male survey respondents. Equitable experiences were consistent across time for the 8 years of the study. Conclusions: Although mentorship is cited as a key factor in mediating gender disparity in medicine, other STEM fields, and the military, the findings suggest that there is equity at the USU undergraduate medical education level. Further studies are needed to understand if disparities in mentorship experiences occur at other stages of a military physician's career, such as graduate medical education, faculty and academic promotion levels.